Providing shape stability of wood composite blanks for manufacture of wood products - Atamanyuk , Volodymyr; Bilyy, Yaroslav (Forestry, Forest, Paper and Woodworking Industry, 2017)
The factors that affect the uniformity of panel workpieces are substantiated. The influence of the thickness of the removed layer from the surface of the workpiece on the process of form-resistance of the shield elements during the calibration, capping and endurance in a dense foot is investigated. It is verified and proved the influence of the veneer moisture on the shape resistance of the shield billets of furniture furniture products in the process of exposure to MDF. The graphical dependence of the deviation from the flatness of the shield blanks, screwed with veneer planed, from the time of exposure in a dense foot is obtained.